PENGARUH STRES KERJA, KEPUASAN KERJA DAN KOMPENSASI TERHADAP INTENSI TURNOVER DI PT. JNE - Fani, Mutiara Novianti; Pawirosumarto, Suharno (SWOT : Jurnal Ilmiah Ilmu Manajemen, 2019)
PT. JNE detected high turnover can be seen based on employee turnover data from 2014 to 2016. The problems that often arise based on pre-reseach is the high level of turnover that can lead to increased intentions of employee turnover. This study aims to determine the effect of Job Stress, Job Satisfaction, and Compensation to Turnover Intention. The type of quantitative descriptive research with explanatory survey approach, the population of all employees of PT JNE number of 100 employees with non-probability sampling technique that is sample saturation / survey, while multiple linear regression analysis data. The results of research have significant influence simultaneously for variable of Work Stress, Job Satisfaction and Compensation to Turnover Intention in PT. JNE. The work stress variable on the dimensions of environmental factors that most dominant influence on Intention Turnover at PT. JNE. It is therefore recommended that the company review the jobdesk of each employee and adjust the fee given, in order to increase the life needs of employees can be fulfilled